(untitled) (Journal of Education and Development, 2022)
Writing is a concrete expression of the ability to pragmatic, as well as an important skill in learning English. In English Curriculum Standard for Compulsory Education (2022), students are expected to be able to use different sentence structures and tenses in their written expressions to describe or introduce people, things or events around them, expressing emotional attitudes, opinions and intentions. In addition, errors in writing can reflect students’ knowledge of pragmatic. The British linguist Pit Corder proposed Error Analysis Theory in the late 1960s and pointed out that errors can be used as a learning tool. Integrating Error Analysis Theory with junior high school students’ writing can help improving their writing skills. Zizhong Falun Junior High School is located in Falun town, Zizhong county, Sichuan Province, which is a rural junior high school. In this study, the writer collected and analyzed the writing samples of students in the midterm examination of grade two in this school, as well as put forward the targeted suggestions.